Integrative and complementary practices in Primary Care: unveiling health promotion - Indiara Sartori Dalmolin; Ivonete Teresinha Schülter Buss Heidemann (Revista Latino-Americana de Enfermagem)
Objective: to understand the use of integrative and complementary practices as a health promotion action. Method: qualitative study, action-participant type, with the application of Paulo Freire’s Research Itinerary, in which 30 Primary Health Care professionals participated. Thematic research was developed with two Primary Care Units, one that used integrative and complementary practices in daily life and another that focused more on allopathic concepts of assistance. To carry out the three stages of the method used, seven Culture Yarning Circles took place. The critical unveiling took place concurrently with the participation of those surveyed. Results: integrative and complementary practices constitute a form of health care, with the purpose of understanding the human being in the health-disease process, making it possible to work with the different aspects that involve them. In this way, they reduce damages resulting from the excessive use of medications, stimulate comprehensiveness and promote health. Conclusion: integrative and complementary practices are resources for health promotion, through comprehensive care and reducing the use of medications.